2021
DOI: 10.3389/fonc.2021.783257
|View full text |Cite
|
Sign up to set email alerts
|

Current Surgical Therapy of Locally Advanced cSCC: From Patient Selection to Microsurgical Tissue Transplant. Review

Abstract: Among the non-melanoma skin cancers (NMSC) the squamous cell carcinoma (SCC) is one of the most challenging for the surgeon. Local aggressiveness and a tendency to metastasize to regional lymph nodes characterize the biologic behavior. The variants locally advanced and metastatic require wide excision and node dissection. Such procedures can be extremely detrimental for patients. The limit of the surgery can be safely pushed forward with a multidisciplinary approach. The concept of skin oncoplastic surgery, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…Although the standard of care remains tumor excision with clear margins, the reconstructive process may be challenging in cases of locally advanced neoplasms [38]. This may imply that the risk of secondary complications could overweigh the benefits of the surgery, and if the second step cannot be successfully accomplished, maybe the entire procedure should be abandoned in favor of other non-surgical treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the standard of care remains tumor excision with clear margins, the reconstructive process may be challenging in cases of locally advanced neoplasms [38]. This may imply that the risk of secondary complications could overweigh the benefits of the surgery, and if the second step cannot be successfully accomplished, maybe the entire procedure should be abandoned in favor of other non-surgical treatments.…”
Section: Discussionmentioning
confidence: 99%
“…For all the above-mentioned reasons, surgeons find the MTB to be particularly beneficial when dealing with complex and advanced cases [38].…”
Section: Discussionmentioning
confidence: 99%
“…Different from the study by Chen et al that observed a significant increase in treatment costs in the advanced stages of the disease, we observed an approximately 4-fold increase in the treatment costs of stage IV compared with stage I, but our results had no statistical significance [ 15 ]. However, the costs may be related to the more complex surgical procedure and to the more careful postoperative medical attention in advanced stages compared to early stages [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Flap surgery is commonly employed for wound repair or tissue transplantation, 7 with the key objective of ensuring flap viability. To achieve optimal surgical outcomes, it is crucial to preoperatively select the most suitable vascular pedicle for blood supply 8 . IRT can provide thermal distribution images of blood vessels, revealing temperature variations in different regions 9 .…”
Section: Introductionmentioning
confidence: 99%
“…To achieve optimal surgical outcomes, it is crucial to preoperatively select the most suitable vascular pedicle for blood supply. 8 IRT can provide thermal distribution images of blood vessels, revealing temperature variations in different regions. 9 Generally, areas with larger vessel diameters and faster blood flow tend to exhibit higher surface temperatures.…”
Section: Introductionmentioning
confidence: 99%